Manganese–nitrogen and gadolinium–nitrogen Co-doped graphene quantum dots as bimodal magnetic resonance and fluorescence imaging nanoprobes. (3rd December 2020) - Lee, Bong Han; Hasan, Md Tanvir; Lichthardt, Denise; Gonzalez-Rodriguez, Roberto; Naumov, Anton V
Abstract: Graphene quantum dots (GQDs) are unique derivatives of graphene that show promise in multiple biomedical applications as biosensors, bioimaging agents, and drug/gene delivery vehicles. Their ease in functionalization, biocompatibility, and intrinsic fluorescence enable those modalities. However, GQDs lack deep tissue magnetic resonance imaging (MRI) capabilities desirable for diagnostics. Considering that the drawbacks of MRI contrast agent toxicity are still poorly addressed, we develop novel Mn 2+ or Gd 3+ doped nitrogen-containing graphene quantum dots (NGQDs) to equip the GQDs with MRI capabilities and at the same time render contrast agents biocompatible. Water-soluble biocompatible Mn-NGQDs and Gd-NGQDs synthesized via single-step microwave-assisted scalable hydrothermal reaction enable dual MRI and fluorescence modalities. These quasi-spherical 3.9–6.6 nm average-sized structures possess highly crystalline graphitic lattice structure with 0.24 and 0.53 atomic % for Mn 2+ and Gd 3+ doping. This structure ensures high in vitro biocompatibility of up to 1.3 mg ml −1 and 1.5 mg ml −1 for Mn-NGQDs and Gd-NGQDs, respectively, and effective internalization in HEK-293 cells traced by intrinsic NGQD fluorescence. As MRI contrast agents with considerably low Gd and Mn content, Mn-NGQDs exhibit substantial transverse/longitudinal relaxivity ( r 2 / r 1 ) ratios of 11.190, showing potential as dual-mode longitudinal or transverse relaxation time ( T 1 or T 2 ) contrast agents, while Gd-NGQDs possess r 2 / r 1 of 1.148 with high r 1 of 9.546 mM −1 s −1 compared to commercial contrast agents, suggesting their potential as T1 contrast agents. Compared to other nanoplatforms, these novel Mn 2+ and Gd 3+ doped NGQDs not only provide scalable biocompatible alternatives as T1/T2 and T1 contrast agents but also enable in vitro intrinsic fluorescence imaging.